Scheme of Smart Home Application Control Based on Cloud Service - Bin Wang; Xiaoling Yang; Dongdi Xiao (Dianxin kexue)
How smart home devices access network,how intelligent control terminals control the smart home equipment,and how smart home devices and application management platform manage users and devices,all the solutions of these problems are changing with the rapid development of smart home application.The application control mode of smart home service was showed,which leads to the key logic hierarchy structure of the application control mode.On the basis of the key logical hierarchy structure,application control scheme based on cloud services was discussed.Finally a summary was given.